Recent investigations into composite sway frames - Demonceau, Jean‐François; Jaspart, Jean‐Pierre (Journal of Civil Engineering and Management, 2004)
A modern design code for composite construction such as Eurocode 4 limits its scope to “non‐sway buildings” with efficient bracing systems. Therefore it gives mainly rules to analyse and to check structural elements like beams, columns, slabs and joints. However, in the last years, the construction of taller buildings and larger industrial halls without wind bracing systems is susceptible to make global instability a relevant failure mode, what is not yet covered by Eurocode 4. For three years, in the framework of a European research project funded by the European Community for Steel and Coal (ECSC), in which Liège University was deeply involved, intensive experimental, numerical and theoretical investigations have been carried out. The latter aimed at improving the knowledge in the field of sway composite frames and at developing appropriate design rules. The rotational behaviour of the beam‐to‐column composite joints is one of the key aspects of the problem to which a special attention has been paid. This paper presents numerical and analytical studies carried out at Liège University, as part of the above European project, with the objective to investigate the behaviour of 2D composite sway frames under static loading. Particular phenomena put into sight through different analyses are illustrated herein. First Published Online: 14 Oct 2010